Benefits from an autobiographical memory facilitation programme in relapsing-remitting multiple sclerosis patients: a clinical and neuroimaging study. Issue 7 (3rd October 2018) - Ernst, Alexandra; Sourty, Marion; Roquet, Daniel; Noblet, Vincent; Gounot, Daniel; Blanc, Frédéric; de Seze, Jérôme; Manning, Liliann
ABSTRACT: While the efficacy of mental visual imagery (MVI) to alleviate autobiographical memory (AM) impairment in multiple sclerosis (MS) patients has been documented, nothing is known about the brain changes sustaining that improvement. To explore this issue, 20 relapsing-remitting MS patients showing AM impairment were randomly assigned to two groups, experimental ( n  = 10), who underwent the MVI programme, and control ( n  = 10), who followed a sham verbal programme. Besides the stringent AM assessment, the patients underwent structural and functional MRI sessions, consisting in retrieving personal memories, within a pre-/post-facilitation study design. Only the experimental group showed a significant AM improvement in post-facilitation, accompanied by changes in brain activation (medial and lateral frontal regions), functional connectivity (posterior brain regions), and grey matter volume (parahippocampal gyrus). Minor activations and functional connectivity changes were observed in the control group. The MVI programme improved AM in MS patients leading to functional and structural changes reflecting (1) an increase reliance on brain regions sustaining a self-referential process; (2) a decrease of those reflecting an effortful research process; and (3) better use of neural resources in brain regions sustaining MVI. Functional changes reported in the control group likely reflected ineffective attempts to use the sham strategy in AM.